Growth and yield performance of castor hybrids under different methods of planting and fertility levels in North Gujarat Agro-climatic region: PERFORMANCE OF CASTOR HYBRIDS UNDER DIFFERENT METHODS OF PLANTING AND FERTILITY - TARANG PATEL,; A L JAT, (Journal of Oilseeds Research, 2022)
A field experiment was conducted to evaluate the yield performance of castor hybrids under different methods of planting and fertility levels at Agronomy Instructional Farm, C P College of Agriculture, Sardarkrushinagar, Gujarat in loamy sand soil. The experiment consisted eight treatment combinations with two hybrids (GCH 7 and GCH 8), two planting methods (Direct seed sowing and Transplanting) and two fertility levels(75% RDF and 100% RDF) were undertaken in randomized block design with factorial concept and replicated four times. Significantly higher number of capsules (88.63) on primary spike, seed yield per plant (686.30 g), 100-seed weight (32.49 g), number of spikes (20.01) per plant, seed yield (3220 kg/ha) and stalk yield (5340 kg/ha) were recorded with GCH 8 hybrid. In plantingmethods, significantly higher number of capsules (89.09) on primary spike, seed yield per plant (688.65 g), number ofspikes (19.60) per plant, seed yield (3230 kg/ha), stalk yield (5361 kg/ha) and available P2O5 (48.7 kg/ha) and S (13.01 mg/kg) after harvest of crop were recorded under direct seed sown castor. 100% RDF registered significantly higher plant height (86.14 cm) at harvest, number of nodes (18.58) per plant, number of capsules (88.60) on primary spike, length of primary (74.57 cm) spikes, seed yield per plant (688.53 g), 100-seed weight (32.00 g), number ofspikes (19.66) per plant, seed yield (3190 kg/ha), stalk yield (5281 kg/ha) and available N, P2O5and S (156 kg/ha, 49.8 kg/ha and 13.35 mg/kg, respectively).